1998
DOI: 10.1111/j.1699-0463.1998.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibromyxoid tumour of soft parts: report of four cases including one mediastinal and one infantile

Abstract: Ekfors, T. O., Kulju, T., Aaltonen, M. & Kallajoki, M. Ossifying fibromyxoid tumour of soft parts: report of four cases including one mediastinal and one infantile. APMIS 106: 1124-1 130, 1998.Four cases of ossifying fibromyxoid tumour of soft parts are described. One of them was in the mediastinum, a hitherto unreported location of this rare neoplasm. Another was removed from the subcutaneous tissue of the head of a two-year-old girl, the youngest patient so far described. A peculiar feature of this tumour wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…The most consistent findings were immunoreactivity of tumor cells for S-100 and the presence of EL by electron microscopy in the majority of cases studied, similar to the original observation of Enzinger et al [1]. These findings led the majority of subsequent authors to favor Schwann cell histogenesis of OFMT [6][7][8][9][10]. However, similarities between peripheral nerve sheath tumors and OFMT seem to be limited [2].…”
supporting
confidence: 78%
“…The most consistent findings were immunoreactivity of tumor cells for S-100 and the presence of EL by electron microscopy in the majority of cases studied, similar to the original observation of Enzinger et al [1]. These findings led the majority of subsequent authors to favor Schwann cell histogenesis of OFMT [6][7][8][9][10]. However, similarities between peripheral nerve sheath tumors and OFMT seem to be limited [2].…”
supporting
confidence: 78%
“…2,3,8,11,18,26,49 However, it is our impression that some of the cases reported as OFTs in patients below the age of 10 years, are more plausibly explained by alternative diagnoses. Examples include a subcutaneous tumor in the head in a 2-year-old with distinct lesional smooth musclelike elements, 8 and a 25-cm S100 protein-positive retroperitoneal tumor with a corded pattern involving nerve roots, more consistent with an epithelioid peripheral nerve sheath tumor. 18 Another tumor composed of interlacing fascicles of spindle cells 3 also seems to be different from OFT.…”
Section: Discussionmentioning
confidence: 98%
“…9 To date, approximately 220 tumors have been published as OFTs. Most of these lesions have had classic morphology, 1,4,7,8,11,13,14,16,[21][22][23][24][25]28,30,32,34,[36][37][38][39][40][43][44][45][46][47]49 but more emphasis has recently been placed on the recognition of atypical and clinically malignant variants. 6,12,19,25,29,35,41,48,49 In 1 large series, it was suggested that either high nuclear grade or high cellularity in combination with a mitotic rate >2 mitoses per 50 HPFs predicts malignant behavior in OFT.…”
mentioning
confidence: 99%
“…In addition to a few large series [1,[4][5][6][7], there are many case reports describing a single or a few cases [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although the extremities, trunk, and head and neck are prevailing sites, unusual locations, such as the retroperitoneum and mediastinum, were also recognized [11,15,19]. OFMT shows characteristic microscopic features: ovoid tumor cells exhibit nodular growth pattern within a fibromyxoid stroma [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Ossifying Fibromyxoid Tumor were reported to be positive for desmin, smooth muscle actin, myosin, and muscle actin, indicating myogenic or leiomyogenic differentiation [11,25]. However, ultrastructural investigations have failed to demonstrate myofilaments and other organelles suggestive of myogenic differentiation [1, 5, 6, 10, 12, 14, 15, 17-20, 24, 26, 28].…”
mentioning
confidence: 99%